De la philosophie de la libération - Enrique Dussel (Cahiers des Amériques Latines)
The objective of this paper is to examine three key concepts that form the main structure of the « modernity/coloniality » group: the coloniality of power, the coloniality of knowledge and the coloniality of being. These three concepts and the articulation among them is what the Colombian philosopher Santiago Castro-Gómez has called « the three-headed hydra ». I will show that coloniality of being is a conceptual synthesis under which the other two are subsumed; this concept expresses the concrete form of domination exercised by colonialism in Latin America and the third world.